2014
DOI: 10.3389/fmicb.2014.00140
|View full text |Cite
|
Sign up to set email alerts
|

Population and genomic analysis of the genus Halorubrum

Abstract: The Halobacteria are known to engage in frequent gene transfer and homologous recombination. For stably diverged lineages to persist some checks on the rate of between lineage recombination must exist. We surveyed a group of isolates from the Aran-Bidgol endorheic lake in Iran and sequenced a selection of them. Multilocus Sequence Analysis (MLSA) and Average Nucleotide Identity (ANI) revealed multiple clusters (phylogroups) of organisms present in the lake. Patterns of intein and Clustered Regularly Interspace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 70 publications
1
36
0
Order By: Relevance
“…The rpoB9 gene of strain C170 was amplified by PCR, using the primers designed by Fullmer et al (2014) andRam Mohan et al (2014). The sequencing primer M13 (18 bp) was added to the 5' end of the degenerate primers to sequence PCR products more efficiently Ram-Mohan et al, 2014).…”
Section: Differential Features Of Strains Cb34mentioning
confidence: 99%
See 2 more Smart Citations
“…The rpoB9 gene of strain C170 was amplified by PCR, using the primers designed by Fullmer et al (2014) andRam Mohan et al (2014). The sequencing primer M13 (18 bp) was added to the 5' end of the degenerate primers to sequence PCR products more efficiently Ram-Mohan et al, 2014).…”
Section: Differential Features Of Strains Cb34mentioning
confidence: 99%
“…The MLSA approach is typically a reliable method that differentiates individual strains, and groups strains into species and species into genera, as well as family-like relationships within the Halobacteriales (Papke et al, 2011). Among the single copy protein-encoding genes investigated previously for evolutionary and taxonomic studies in haloarchaea, the rpoB9 gene has been reported to be very successful in overcoming the above disadvantages of the 16S rRNA gene marker (Walsh et al, 2004; Enache et al, 2007; Minegishi et al, 2010;Papke et al, 2011;Fullmer et al, 2014;Ram-Mohan et al, 2014).Aran-Bidgol hypersaline lake is a natural ecosystem located in the central desert area of Iran, formed in the Pliocene period. The pH of the lake brine is neutral, the predominant salts are NaCl, Na 2 SO 4 , MgCl 2 and MgSO 4 with trace amounts of carbonates, and it is considered a thalassohaline lake (Makhdoumi-Kakhki et al, 2012a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the best-studied hypersaline system with respect to its microbiology with nearly continuous study for >35 years [Reviewed in [17]]. The first metagenomic studies on this saltern were focused on the saturated NaCl ponds and showed that the community was dominated by Haloquadratum walsbyi, which demonstrated tremendous genome plasticity and high gene content variability among close relatives [18,19], features later observed in other haloarchaeal species [20,21] and in Salinibacter ruber [22].…”
Section: Introductionmentioning
confidence: 99%
“…6) (35) suggests that the long-term survival of inteins does not include the homing cycle going to completion; instead, fitness differences between organisms with and without inteins appear to play a role in the long-term coexistence of the HEN with alleles containing empty target sites. In our simplifying simulations, the HEN was found to completely invade a homogeneous population close to its carrying capacity; however, natural populations of H. volcanii are neither homogeneous, nor do they exist in a constant environment.…”
Section: Discussionmentioning
confidence: 99%